The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1590/s1677-5538.ibju.2023.0546
|View full text |Cite
|
Sign up to set email alerts
|

Lower Urinary Tract Symptoms in a prospective cohort of COVID-19 survivors

Cristiano M. Gomes,
Marcelo Hisano,
Julia D. Souza
et al.

Abstract: Purpose:To analyze the prevalence of lower urinary tract symptoms (LUTS) in patients who survived moderate and severe forms of COVID-19 and the risk factors for LUTS six months after hospitalization. Materials and Methods:In this prospective cohort study, patients were evaluated six months after hospitalization due to COVID-19. LUTS were assessed using the International Prostate Symptom Score. General health was assessed through the Hospital Anxiety and Depression Scale and the EQ5D-L5 scale, which evaluates m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Dr. Gomes and collegues from Brazil performed in page 287 ( 3 ) an interesting study about theurinary tract symptoms in a prospective cohort of COVID-19 survivors and concluded that LUTS are highly prevalent and bothersome six months after hospitalization due to COVID-19. Assessment of LUTS may help ensure appropriate diagnosis and treatment in these patients.…”
mentioning
confidence: 99%
“…Dr. Gomes and collegues from Brazil performed in page 287 ( 3 ) an interesting study about theurinary tract symptoms in a prospective cohort of COVID-19 survivors and concluded that LUTS are highly prevalent and bothersome six months after hospitalization due to COVID-19. Assessment of LUTS may help ensure appropriate diagnosis and treatment in these patients.…”
mentioning
confidence: 99%